(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Working motivation is the desire, voluntary of employees to increase efforts towards a certain goal or result. For hospitals, the work motivation of medical staff contributes to improving the quality and efficiency of medical service delivery. Objective: Analyzing some related factors to working motivation of nurses at Nghia Lo general hospital, Yen Bai province in 2021 Methods: Cross-sectional study Results and conclusion: The percentage of nurses with working motivation was 78.9% (3.68 points ± 0.33). There are 8 factors that are statistically significantly related to the working motivation of nurses, including: Age, main income earner in the family, average income/month, seniority, type of labor, relationship workplace, work overload and opportunities to use personal abilities (p<0.05).